2017
DOI: 10.1016/j.stem.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Recruited Monocytes and Type 2 Immunity Promote Lung Regeneration following Pneumonectomy

Abstract: Summary To investigate the role of immune cells in lung regeneration, we used a unilateral pneumonectomy model that promotes the formation of new alveoli in the remaining lobes. Immunofluorescence and single cell RNA- sequencing found CD115+ and CCR2+ monocytes and M2-like macrophages accumulating in the lung during the peak of type 2 alveolar epithelial stem cell (AEC2) proliferation. Genetic loss of function in mice and adoptive transfer studies revealed that bone marrow-derived macrophages traffic to the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
210
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(231 citation statements)
references
References 104 publications
11
210
0
Order By: Relevance
“…Cytometric analysis demonstrated increased numbers of CD11b + macrophages and expression of RNAs associated with M2 macrophage activation during regeneration. Studies of lung regeneration after partial pneumonectomy support the concept that interactions among activated macrophages and lung parenchymal cells create a proliferative microenvironment (22). In the present study, regeneration was associated with marked increase in inflammatory cell expression of ARG1 and other markers of atypical macrophage activation (M2-like), including RETNLA and CD206, proposed to contribute to repair processes (22,41,42).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Cytometric analysis demonstrated increased numbers of CD11b + macrophages and expression of RNAs associated with M2 macrophage activation during regeneration. Studies of lung regeneration after partial pneumonectomy support the concept that interactions among activated macrophages and lung parenchymal cells create a proliferative microenvironment (22). In the present study, regeneration was associated with marked increase in inflammatory cell expression of ARG1 and other markers of atypical macrophage activation (M2-like), including RETNLA and CD206, proposed to contribute to repair processes (22,41,42).…”
Section: Discussionsupporting
confidence: 72%
“…During repair, BrdU incorporation was present in inflammatory, endothelial, epithelial, and stromal cells, and it was consistently observed in cell clusters containing diverse cell types. Interactions between alveolar macrophages and AT2 cells were previously suggested to enhance cell survival, via mitochondrial transfer or suppression of inflammation (22,(38)(39)(40). In the present study, CD45 + macrophages were frequently found in close proximity to proliferating AT2 cells.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…RSV infection promotes accumulation of IL-13-expressing ILC2s in the lung, which associates with increased type 2 inflammatory responses (470), suggesting at least one connection of ILC2s to lower respiratory infection. ILC2s help repair and regenerate injured lung tissue (44,279,333), but ILC2-mediated repair after pneumonia specifically is presently speculative. ILC3s are perhaps the most relevant to pneumonia biology and acute pulmonary inflammation, particularly with regards to their influence on IL-17-mediated defense.…”
Section: Innate Lymphocytesmentioning
confidence: 99%